Pelatihan Pembuatan Media Vertikultur dengan Memanfaatkan Limbah Plastik pada Lahan Pekarangan - Muhammad Farid Nasrulloh; Ospa Pea Yuanita Meishanti; Mochamad Syafiuddin Shobirin; Siti Khoirun Naazilah; Rissalatul Illiyin; Wisnu Siwi Satiti (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2021)
Yard land for plant cultivation is an action in improving people's welfare. The yard of the house is generally not too wide so that if it is used as a land for plant cultivation, it will be more efficient, so there is a need for cultivation innovations that can be carried out in an easy, practical way to maintain and can streamline a narrow yard. Based on the results of the analysis, the problems that need to be resolved related to the planned community service activities are as follows: (1) lack of public knowledge about the use of yard land for food crops using verticulture technology based on plastic waste, (2) lack of public awareness to manage plastic waste, (3) the community, especially housewives, have not made optimal use of their home yards for plants that can be used as daily food needs, (4) the community's lack of interest in creating a clean environment, aesthetic value, and economic value. The method used is socialization which aims to increase public knowledge in utilizing the yard of the house with verticulture techniques. This community service activity in the form of socialization has provided benefits to participants, the perceived benefit is the increase in the level of knowledge of PKK mothers and also IPNU-IPPNU youth about vegetable cultivation techniques with verticulture techniques. This activity was considered quite successful in increasing the skills of the participants.